Research progress on gastric cancer-associated microbiome and important microbial mechanisms - Jiang Xiaowen; Zhang Jingying; Zhou Tong; Li Wenqing; Pan Kaifeng; Zhang Yang (生物医学转化)
Gastric cancer (GC) remains one of the major threats to global health, imposing a substantial disease burden. Its pathogenesis is complex and likely influenced by the interplay of multiple environmental, genetic and microbial factors. Advances in rapidly evolving microbiome detection technologies suggest that the gastric mucosal microbiota including Helicobacter pylori, a key carcinogenic factor, may interact and play synergistic roles in gastric cancer initiation and progression. This review summarizes recent advances in GC-associated microbiome research, systematically organizing and analyzing the pivotal roles of gastric microbiota in cancer tumorigenesis, progression and prognosis. Furthermore, it examines the potential mechanisms by which the key gastric microbes may contribute to carcinogenesis, providing a scientific foundation for future etiological investigations and early diagnosis and prevention targeting microbiome-related GC.